PENGARUH COMPANY SIZE, PROFITABILITAS, SPESIALISASI AUDITOR, REPUTASI AUDITOR DAN KOMPLEKSITAS OPERASI TERHADAP AUDIT REPORT LAG ( Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2018) - Aisyah Nur; Andreas Andreas; Hariyani Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research was conducted with the aim of proving and analyzing the effect of Company size, Profitability, Auditor Specialization, Auditor Reputation, and Operational Complexity on Audit Report Lag. This research was conducted at all Manufacturing companies listed on the IDX for the 2016 - 2018 period. The sampling method used was purposive sampling technique, with a total sample of 111 companies. The analysis technique used is multiple regression with dummy variables using the SPSS 21 program. Based on the analysis, it is found that the complexity of the operation has a positive effect on the audit report lag, while the company size, profitability, auditor specialization, and auditor reputation have a negative effect on the audit report lag. Simultaneously, company size, profitability, auditor specialization, auditor reputation, and operation complexity have a significant effect on audit report lag.Keywords: Audit Report Lag, Company Size, Profitability, Auditor Specialization, Auditor Reputation, Operation Complexity